Kinetic and thermodynamic analysis of iron oxide reduction by graphite for CO 2 mitigation in chemical‐looping combustion - Ubando, Aristotle T.; Chen, Wei Hsin; Show, Pau Loke; Ong, Hwai Chyuan (John Wiley & Sons, 2020)
Chemical-looping combustion (CLC) provides a platform to generate energy streams while mitigating CO2 using iron oxide as a carrier of oxygen. Through the reduction process, iron oxide experiences phase transformation to ultimately produce metallic iron. To understand iron oxide reduction characteristics and optimally design the fuel reactor, kinetic and thermodynamic analyses were proposed, utilizing graphite. This study aims to evaluate the reduction behavior under the non-isothermal process of various mixture ratios of hematite and graphite via thermogravimetric analysis with simultaneously evaluating evolved gases using a Fourier transform infrared spectrometer. The Coats-Redfern model was employed to approximate the kinetic and thermodynamic parameters which assessed the different reaction mechanisms together with the distributed activation energy model (DAEM). The results revealed that the hematite-to-graphite ratio of 4:1 had the highest reduction degree and had three distinct peaks representing three iron oxide reduction phases. The zero-order reaction mechanism agreed with the experimental results compared with other reaction models. The thermodynamic analysis showed an overall endothermic spontaneous reaction for the three phases which signified the direct reduction of the iron oxides. The DAEM result validated a stepwise reduction of iron oxides to metallic iron. The study aids the optimal design of the CLC fuel reactor for enhanced system performance. © 2020 John Wiley & Sons Ltd